Analisis Pengaruh PDRB, Belanja Daerah, Jumlah Wisatawan, dan Jumlah Objek Wisata Terhadap Pendapatan Asli Daerah di Provinsi Daerah Istimewa Yogyakarta Tahun 2016 -2022 - Alifa, Zahradiva Nada; Nasir, Muhammad Safar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Regional governments must optimize local original income by maximizing existing capabilities without violating provisions. PAD as a regional recipient, illustrates the level of regional independence. This research aims to determine the influence of GRDP, regional spending, number of tourists and number of tourist attractions on local revenue in the Special Region of Yogyakarta Province in 2016 - 2022. The data used is secondary data sourced from Bappeda. The data used in this research are GRDP, regional spending, number of tourists and number of tourist attractions in 2016-2022. The data analysis tool uses panel data regression. The results of this research show that GRDP has no effect, regional spending has no effect, the number of tourists has no effect and the number of tourist attractions has no effect on local revenue.